Cell Growth Inhibition, DNA Fragmentation and Apoptosis-Inducing Properties of Household-Processed Leaves and Seeds of Fenugreek (Trigonella Foenum-Graecum Linn.) against HepG2, HCT-116, and MCF-7 Cancerous Cell Lines - Shaimaa G. Abdel Salam; Mohamed M. Rashed; Nabih A. Ibrahim; Emam A. Abdel Rahim; Hadeil Muhanna Alsufiani; Rasha A. Mansouri; Mohamed Afifi; Ammar Al-Farga (Current Issues in Molecular Biology, 2023)
Household processing of fenugreek seeds and leaves, including soaking, germination, and boiling of the seeds, and air-drying of the leaves, has improved the levels of human consumption of the bitter seeds and increased the shelf life of fresh leaves, respectively. The potential anticancer activity of either unprocessed or processed fenugreek seeds or leaves and the relative expression of pro-apoptotic and anti-apoptotic genes of the studied cancerous cell lines exposed to IC50 crude extracts was investigated to observe the apoptotic-inducing property of this plant as an anticancer agent. The protein expression of IKK-α and IKK-β, as inhibitors of NF-KB which exhibit a critical function in the regulation of genes involved in chronic inflammatory disorders, were studied in the tested cancerous cell lines. In this study, the anticancer activity of household-processed fenugreek leaves and seeds against HepG2, HCT-116, MCF-7, and VERO cell lines was measured using an MTT assay. DNA fragmentation of both HepG2 and MCF-7 was investigated by using gel electrophoresis. RT-PCR was used to evaluate the relative expression of each p53, caspase-3, Bax, and Bcl-2 genes, whereas ELISA assay determined the expression of caspase-3, TNF-α, and 8-OHDG genes. Western blotting analyzed the protein-expressing levels of IKK-α and IKK-β proteins in each studied cell line. Data showed that at 500 µg mL−1, ADFL had the highest cytotoxicity against the HepG2 and HCT-116 cell lines. Although, each UFS and GFS sample had a more inhibitory effect on MCF-7 cells than ADFL. Gel electrophoresis demonstrated that the IC50 of each ADFL, UFS, and GFS sample induced DNA fragmentation in HepG2 and MCF-7, contrary to untreated cell lines. Gene expression using RT-PCR showed that IC50 doses of each sample induced apoptosis through the up-regulation of the p53, caspase-3, and Bax genes and the down-regulation of the Bcl-2 gene in each studied cell line. The relative expression of TNF-α, 8-OHDG, and caspase-3 genes of each HepG2 and MCF-7 cell line using ELISA assays demonstrated that ADFL, UFS, and GFS samples reduced the expression of TNF-α and 8-OHDG genes but increased the expression of the caspase-3 gene. Protein-expressing levels of IKK-α and IKK-β proteins in each studied cell line, determined using Western blotting, indicated that household treatments decreased IKK-α expression compared to the UFS sample. Moreover, the ADFL and SFS samples had the most activity in the IKK-β expression levels. Among all studied samples, air-dried fenugreek leaves and unprocessed and germinated fenugreek seeds had the most anti-proliferative and apoptotic-inducing properties against human HepG2, MCF-7, and HCT-116 cell lines, as compared to the VERO cell line. So, these crude extracts can be used in the future for developing new effective natural drugs for the treatment of hepatocellular, breast, and colon carcinomas.